SCIENTOMETRIC ANALYSIS OF SCIENTIFIC LITERATURE ON NEUROMARKETING TOOLS IN ADVERTISING - Lina Pilelienė; Ahmed H. Alsharif; Ibrahim Bader Alharbi (Baltic Journal of Economic Studies, 2022)
Neuromarketing (NM) is a relatively new area of marketing that involves innovative technological changes in the marketing research process and the tools and methods used. Considering the novelty of the domain, the subject of the study is chosen to be articles published in scientific literature describing neuromarketing tools used in advertising. This study examined articles in the field of advertising that used neuromarketing techniques to measure consumers' neural and physiological responses to advertising, which has not yet been covered in the literature. Methodology. To fill the gap in the literature, the authors, guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol, selected relevant articles and conducted a bibliometric analysis to identify global trends and developments in the field of advertising and neuromarketing. From the Web of Science (WoS) database, 41 articles published between 2009 and 2020 were extracted and analyzed. Purpose of the study was to establish a background for advertising research based on the application of NM tools. The findings revealed that Spain was the most productive country with eleven papers published in a domain of advertising research, followed by Italy and the USA with eight and seven papers, respectively. Among academic institutions, Sapienza University Rome was recognized as the leading academic organization with three articles. As for the most productive journals, Frontiers in Psychology was the most cited journal with eight articles and 29 total citations (TC). As the highest productive author, Babiloni, F. with two papers and 68 TCs by 2020 was identified. Keyword analysis showed that "advertising" (27 occurrences and 127 total references) is the most frequently used keyword. The analysis of co-occurrence of keywords showed that NM focused on marketing research such as advertising (12 occurrences, 63 total link strength (TLS)), followed by brain processes such as attention, emotions and memory. The paper titled “Neuromarketing: The new science of consumer behavior” was the most-cited paper with 152 TCs. Conclusion of the study. This study presents a brief overview of the latest universal areas of neuromarketing and advertising research. The findings suggest that neuroscientific methods and techniques are extremely important for mapping consumers' neural and physiological responses to advertising.